Share Rose, Get Fun: The Influence of Donation on Happiness - Wu, Yuan-yang; Yu, Yi-tong; Yao, Yi-dan; Su, Mo-han; Zhang, Wen-chao; Ti, Shi-ming; Lin, Xue-yu; Zhang, Shuo; Zhang, Si-qing; Yang, Hua-lei (Frontiers in Sociology, 2021)
The coronavirus 2019 pandemic has reinforced the need for a third force in society beyond the market and government: volunteerism and donation. However, as there is little literature on the impact of donation on individual well-being in China.This study examines individual donations in China to answer the question of whether helping others makes us happier and to provide policy implications for the Chinese context. Based on the 2012 China General Social Survey (CGSS) data and using ordered logit and OLS as benchmark models, this study finds that donation can significantly increase individual happiness. After using propensity score matching (PSM) to eliminate the possible impact of self-selection, the above conclusion remains robust. After a split-sample discussion, it is found that this effect is more pronounced under completely voluntary donation behavior, which is consistent with the empirical results and not affected by economic factors, indicating that the effect of happiness enhancement at the time of donation does not vary significantly depending on the individual’s economic status. This study contributes to the literature on donation behavior by examining the impact of donation behavior on donors’ subjective happiness in China, and further identifies subjective happiness differences, as between voluntary and involuntary donations, thereby providing theoretical and empirical support for the formulation of policies for the development of donation institutions in China.